Optimal operation model of integrated energy system for industrial plants considering cascade utilisation of heat energy. Issue 3 (10th December 2019) - Mu, Chenlu; Ding, Tao; Zeng, Ziyu; Liu, Peiyun; He, Yuankang; Chen, Tianen
Abstract : As the energy crisis becomes more prominent, the issue of energy conservation and recycling is urgent. For large‐scale industrial plants, there are various forms of heat energy resources with different grades and energy storages. This study presents the detail modelling of all equipment in the integrated energy system to specify the physical operational constraints. Furthermore, an optimisation model is set up to minimise the total cost of an individual industrial plant, with the consideration of energy production equipment, energy conversion equipment and energy storage equipment in the plant. In particular, the relationship among the heat energy with different grades is described to characterise the cascade utilisation of the heat energy. Finally, a material processing factory with multi‐grade heat energy is simulated to verify the effectiveness of the proposed model with energy cascade utilisation.